2013
DOI: 10.1016/j.radmeas.2012.12.016
|View full text |Cite
|
Sign up to set email alerts
|

Measurement of multi-slice computed tomography dose profile with the Dose Magnifying Glass and the MOSkin radiation dosimeter

Abstract: . (2013). Measurement of multislice computed tomography dose profile with the Dose Magnifying Glass and the MOSkin radiation dosimeter. Radiation Measurements, 55 51-55. Measurement of multi-slice computed tomography dose profile with the Dose Magnifying Glass and the MOSkin radiation dosimeter AbstractThis study describes the application of two in-house developed dosimeters, the Dose Magnifying Glass (DMG) and the MOSkin dosimeter at the Centre for Medical Radiation Physics, University of Wollongong, Australi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 13 publications
0
5
0
Order By: Relevance
“…Previous research reported that the sensitivity of the MOSkin detector for 150 kVp xray beam (effective energy 64.87 keV) was approximately 6.70 mV cGy −1 , which was measured in comparison with EBT2 film. 41 The sensitivity of the MOSkin detector in a megavoltage beam was 2.63 ± 0.01 mV cGy −1 . 42 The higher sensitivity measured at lower beam energy is due to the increasing dominance of photoelectric absorption and consequently, an F.…”
Section: A Detector Calibrationmentioning
confidence: 95%
See 1 more Smart Citation
“…Previous research reported that the sensitivity of the MOSkin detector for 150 kVp xray beam (effective energy 64.87 keV) was approximately 6.70 mV cGy −1 , which was measured in comparison with EBT2 film. 41 The sensitivity of the MOSkin detector in a megavoltage beam was 2.63 ± 0.01 mV cGy −1 . 42 The higher sensitivity measured at lower beam energy is due to the increasing dominance of photoelectric absorption and consequently, an F.…”
Section: A Detector Calibrationmentioning
confidence: 95%
“…The percentage depth-dose response of the MOSkin detector was investigated previously, 41,45 which compared the MOSkin detector response with Markus chamber and Monte Carlo simulations in water. In their reports, the MOSkin detector showed an over-response compared with the Markus chamber measurements, 41 while Monte Carlo simulations showed MOSkin to have good agreement with simulated water response (±3%). 45 In this study, Fig.…”
Section: E Depth-dose Datamentioning
confidence: 99%
“…The physical performance of this dosimeter was well documented in the literature for external beam radiotherapy [27, 28], interventional radiology procedures [22] and diagnostic radiology dosimetry [16, 17]. …”
Section: Methodsmentioning
confidence: 99%
“…The p-channel MOSFETs (brand named “MOSkin”) together with a portable reader were supplied by the Center of Medical Radiation Physics (CMRP), University of Wollongong, Australia. The physical performance of this dosimeter was well documented in the literature for external beam radiotherapy [ 27 , 28 ], interventional radiology procedures [ 22 ] and diagnostic radiology dosimetry [ 16 , 17 ].…”
Section: Methodsmentioning
confidence: 99%
“…The use of Gafchromic films has been used by medical physicist in developing countries[14] [15]; as well as in developed ones. Such trend proves that radiochromic films are available, affordable and reliable dosimeters that maybe used worldwide[16].…”
mentioning
confidence: 98%